Effects of pyrimethanil on pollen meiosis of tomato plant (Lycopersicon lycopersicum Mill.) (Bangladesh Journal of Botany, 2008)
Effects of Mythos SC 300 (300 g/l pyrimethanil), a fungicide on tomato plants were studied by observation of pollen meiosis. The fungicide was applied at double the recommended dosage (250 ml/100 l tap water). The anthers of flower bud fixed in Carnoy's fluid were stained with 2% aceto-orcein. The fungicide caused various anomalies in pollen meiosis, decrease in pollen yield and consequently influenced future seed formation.